Mobile application in al-Shafie poetry - Din, N.M.B.N.; Wahid, N.A.; Din, N.M.N.; Ismail, N.A.B.; Zakaria, R. (2020)
The use of mobile applications has grown rapidly in the world of science and technology. Besides, Internet access capability, this application also has operating system just like a computer but in a smaller, lightweight form that can be carried anywhere. Therefore, this application should be widely used especially as an educational learning medium because it facilitates every business. The purpose of this concept paper paper is to discusses the significance and effect of using mobile applications on poetry and literature in general. The study of mobile application in language and literature involves the used of qualitative approach with exploratory analysis methods to obtain more accurate and scientifics results.T he results shown that mobile applications will facilitate improvements in language learning and literature. The use mobile application in language and literature review viewed very well.